Autumn rose a dark heroine novel - Gibbs, Abigail (New York William Morrow Paperbacks, 2014)
"Autumn Rose lives in a sleepy seaside town in the south-west of England, but buried deep under the surface of her quiet life are dark secrets. Her grandmother is dead, murdered eighteen months before, and the whirling social scene of London in which she was brought up is a world away. Even worse, at her new school she is shunned and condemned - all because of the swirling marks on her skin that prevent her from blending in the crowd. But the appearance of a handsome young man at her school - who has the same curious markings as Autumn Rose - sends her world into turmoil. Suddenly the marks are cool and Autumn is thrust into the limelight, but her sudden popularity brings danger as her secrets threaten to come to light. Plus, there is the fact that Autumn keeps dreaming of a human girl who is about to be seduced by a very dark Prince... and Autumn must figure out how to save her before it is too late"--
1
Keywords: FICTION / General; FICTION / Romance / Paranormal; Family secrets -- Fiction; Young women -- Fiction; Fantasy fiction; Romantic suspense fiction